(untitled) (River Edge, N.J., 2004)
The symposium "Computational and Group-Theoretical Methods in Nuclear Physics" was organized to celebrate the 60th birthday of Jerry P Draayer, who is Professor of Physics, Lousiana State University, and President of the Southeastern Universities Research Association (SURA). The focus of the meeting was on computational and algebraic approaches to the nuclear many-body problem. The presentations highlighted recent experimental and theoretical developments in nuclear structure physics.
Keywords: Nuclear physics,Vật lý hạt nhân; Mathematics,Toán học